PANGAN DAN DAYA SERAP TENAGA KERJA INDUSTRIALI DI KABUPATEN MOROWALI - Hadisuddin Bolong; Abd Hakim; Zaiful; Nurfazila (Kinesik, 2023)
Industrialization has massively impacted to low level of food availability, also it has triggered labor absorp competition at industrial companies. This study aims to identify condition of the availability of production land and employment opportunities for local communities in industrial areas in Morowali regency, Central Sulawesi, The study outcomes show that agricultural production lands in the border areas to the industrial parks are still available, alhough it seems not yet fully able to meet the food needs of community due to high demand. The demands of agriculture products esepcially food needs (vegetablea and rice) and also livestock products in this area is too much high both to meet the needs of residents, as well as for companies to meet the consumption needs of their labors, while the local community’s lands shifted and are designated for permanent or rented housing due to high demand of housing in this area. Labor opportunities both in agriculture sector and industry have significant increased. The resident’s ecnomic income in this area relatively growed up. However, along with the economic growth, social probles often arise, such as drugs and alcohol abuse.